Microbial approaches in fabrication of nanoscale materials effectively enhance the antimicrobial and crop protection potential–A review - Ved Prakash Giri; Madhuree Kumari (Plant Nano Biology, 2023)
Nanotechnology is continuously marking its presence in sustainable agriculture and crop protection. Microbially synthesized nanomaterials bear an additional advantage over their chemical counterparts in being eco-friendly, economical and synergistic effects of microbial metabolites. Many researchers have reported the enhanced antimicrobial effects of microbially synthesized nanomaterials in crop protection in an environmental-friendly manner. The nanomaterials do not only kill the pathogen directly but also have shown their role as biotic elicitors, modulating the plants’ immune responses, overexpression of defense-related genes, modulation of oxidative stress and changing the ‘omics’ of the plant system. Despite the numerous advantages in agriculture system, certain risks are associated with nanomaterials. Phytotoxicity, eco-toxicity, concentration optimization, impact on native microbiota and the safe use of plants for animal consumption are some of the challenges which require extensive research. Further, strict regulatory authorities across the world regarding the use of nanomaterials, costing, scaling-up and optimizing the microbial condition for the synthesis of nanomaterials are certain steps to ensure the effective use of microbially engineered nanomaterials in the field conditions.